Femoral Artery Trauma: It is a Challenge - Martínez, Bertha Zenaida Acevedo; Sánchez, Morelos Adolfo García; Rodríguez, Andrés Armendáriz; García, Mariana Cuapio; Álvarez, Diana Lizette Estrada; Vázquez, Juan Pablo Rayas; Muñoz, Susana Alejandra Arzate; Contreras, Carlos Héctor Eguía; Delgado, Francisco Javier Juárez (British Journal of Healthcare and Medical Research, 2024)
Introduction: in Mexico there is a high rate of violence in men, as there is throughout the world, with a mortality rate from homicides as alarming as the sixth cause of death in 2023; furthermore, those who become survivors of aggression consequently have temporary or mostly permanent and disabling consequences. Objective: presentation of a case. Method: 26-year-old male who is attacked by third parties, on the left thigh he has a cutting wound in the left inguinal region with dimensions of 2 x 1 cm, with the presence of an evolving hematoma of more than 10 cm., he undergoes surgery. emergency and in the vascular examination a lesion of the superficial femoral artery was identified 5 cm from the division of the common femoral artery complex. Discussion: in most cases the diagnosis of femoral artery trauma is immediately apparent, however, deep rupture of the femoral artery must also be considered. The surgical options regarding femoral artery repair technique will depend on each case: vein graft, end-to-end anastomosis, Fogarty thrombectomy, ligation, arterial repair, use of prosthetic graft, use of patch and arterial bypass. At the level of the femoral vein, its repair is ligation and venous repair, anecdotally. Conclusions: vascular injuries of the femoral arteries are a real challenge for the Trauma Surgeon of this Country, since they put in check the ability to resolve the surgical emergency in a correct, technical, and ethical way. However, despite the lack of supplies and poor infrastructure conditions of the Health System, it still manages to make a difference.